Critical Consciousness-Based HIV Prevention Interventions for Black Gay and Bisexual Male Youth. Issue 1 (2nd January 2019) - Harper, Gary W.; Jadwin-Cakmak, Laura; Cherenak, Emily; Wilson, Patrick
Abstract: Black gay/bisexual male youth are one of the groups most affected by HIV in the United States, but few behavioral interventions have been created specifically to address this health inequity. Oppression related to these youths' multiple social identities—including racism, heterosexism, and HIV stigma—contribute to increased health risks. Primary and secondary HIV prevention interventions created specifically for Black gay/bisexual male youth that address the negative impact of oppression are urgently needed. We present empowerment as a framework for understanding how oppression affects health, and critical consciousness as a tool to be utilized in behavioral interventions. This approach helps to move Black gay/bisexual male youth from a place of oppression and powerlessness that leads to elevated health risks to a position of empowerment that promotes feelings of control and participation in healthy behaviors. Finally, we present a case example of our own critical consciousness-based secondary HIV prevention intervention created specifically for Black gay/bisexual male youth.